160 UMP Kilau Volunteers, UMPH plant 2,000 trees - Nor Salwana, Mohammad Idris (2022)
JERANTUT, 12 August 2022 - A total of 160 students from Universiti Malaysia Pahang (UMP) and UMP Holdings Sdn. Bhd. participated in the Environmental Sustainability programme in collaboration with the Pahang State Forestry Department to plant about 2,000 tree of the species Merawan Siput Jantan, Balau Pasir, Keruing Kertas, Kembang Semangkuk, Meranti Tembaga and Meranti Sarang Punai in the Tekam Forest Reserve.